Randomised clinical trial: vercirnon, an oral CCR9 antagonist, vs. placebo as induction therapy in active Crohn's disease. Issue 10 (23rd September 2015) - Feagan, B. G.; Sandborn, W. J.; D'Haens, G.; Lee, S. D.; Allez, M.; Fedorak, R. N.; Seidler, U.; Vermeire, S.; Lawrance, I. C.; Maroney, A. C.; Jurgensen, C. H.; Heath, A.; et al.
Summary Background Many patients with active Crohn's disease do not adequately respond to therapies, highlighting the need for new treatments. Aims To conduct a randomised, double‐blind, placebo‐controlled phase 3 study to assess the efficacy and safety of vercirnon, an oral inhibitor of CC chemokine receptor‐9, for the treatment of patients with moderately‐to‐severely active Crohn's disease. Methods Patients with a Crohn's Disease Activity Index (CDAI) of 220–450, plus evidence of active disease (endoscopically confirmed or elevation of both C‐reactive protein and faecal calprotectin), who had failed corticosteroid or immunosuppressant therapy were enrolled. Patients were equally randomised to receive placebo, vercirnon 500 mg once daily or vercirnon 500 mg twice daily. The primary endpoint was clinical response, defined as a 100‐point decrease in CDAI from baseline to week 12. Results Six hundred and eight patients were randomised. Patient characteristics and baseline demographics were similar among the groups. The proportions of patients achieving a clinical response were 25.1%, 27.6% and 27.2% for placebo, once daily and twice daily respectively; treatment differences were not significant (2.5%; 95% confidence interval, CI −6.1% to 11.0%, P = 0.546 for once daily vs. placebo, and 2.1%; 95% CI −6.5% to 10.7%, P = 0.648 for twice daily vs. placebo). Adverse events were reported in 69.8%, 73.3% and 78.1% with serious adverse events in 8.9%, 5.9%, and 6.0% of patients in the placebo, once‐daily and twice‐daily groups, respectively. Conclusions We did not demonstrate efficacy of vercirnon as an induction therapy in patients with moderately‐to‐severely active Crohn's disease; its effect in maintenance therapy was not addressed.